MOTIVATION OF THE VALUE ATTITUDE TO THE HEALTH OF STUDENTS OF CHEMICAL SPECIALTIES IN THE PROCESS OF THEIR PROFESSIONAL TRAINING - Rodyhina, V. P.; Kurii, O. V.; Babadzhanian, V. V. (Rehabilitation and Recreation, 2022)
One of the urgent and important medical and social problems at the present stage is to preserve and strengthen the health of young people. Attention to the problem of forming motivation for the value of health attitudes of student youth is explained by the fact that the level of student health is a significant share in the population structure and forms in the future labor resources of our country. To form value attitudes to their health in students should begin with raising the level of health culture, increasing the level of physical health, the formation of active self-development and self-sufficiency. Many students of chemistry are exploiting the most accessible resource – health. Incentives to get an education, a profession, a good financial position are much higher than to maintain and improve health, ie. Health is seen primarily as an instrumental value that contributes to the achievement of life goals, rather than as a value that contributes to long and fulfilling life. The article considers the role of motivation in the formation of values in the health of students of chemical specialties. Students of chemical specialties, despite their future professional activities, which are carried out in conditions of exposure to harmful chemicals, spend little time and effort to maintain their own health. The level of awareness of first-year chemistry students in leading a healthy lifestyle is determined. To increase the effectiveness of motivating students of chemical specialties to value their health, a health model was developed, which is based on an integrated approach and the relationship of educational and educational work throughout the study period. The educational process in the university should be organized with a focus on preserving and strengthening the health of students, means and methods of health measures should be aimed at the conscious development of a healthy student.